2004
DOI: 10.1051/0004-6361:20040538
|View full text |Cite
|
Sign up to set email alerts
|

A model for quasi-spherical magnetized accretion flow

Abstract: Abstract.A model for axisymmetric magnetized accretion flow is proposed. The dominant mechanism of energy dissipation is assumed to be the magnetic diffusivity due to turbulence in the accretion flow. In analogy to the advection-dominated accretion flow (ADAF) solutions, a constant fraction of the resistively dissipated energy is stored in the accreting gas and the rest is radiated. We first introduce the general self-similar solutions which describe a resistive and nonrotating flow with purely poloidal magnet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Consequently, the role of the magnetic fields on ADAFs has been analyzed in detail by a number of investigators (Bisnovatyi-kogan & Lovelace 2001;Akizuki & Fukue 2006, hereafter AF06;Shadmehri 2004, hereafter Sh04; Ghanbari et al, 2007;Bu, Yung, & Xie 2009;Khesali & Faghei 2009, hereafter KF09). The existence of the toroidal magnetic field has been proven in the outer regions of the discs of young stellar objects (YSOs; Aitken et al 1993;Wright et al 1993) and in the Galactic center Chuss et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the role of the magnetic fields on ADAFs has been analyzed in detail by a number of investigators (Bisnovatyi-kogan & Lovelace 2001;Akizuki & Fukue 2006, hereafter AF06;Shadmehri 2004, hereafter Sh04; Ghanbari et al, 2007;Bu, Yung, & Xie 2009;Khesali & Faghei 2009, hereafter KF09). The existence of the toroidal magnetic field has been proven in the outer regions of the discs of young stellar objects (YSOs; Aitken et al 1993;Wright et al 1993) and in the Galactic center Chuss et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of a magnetic field on the disc were also studied (see Balbus & Hawley 1998; Kaburaki 2000; Shadmehri 2004; Meier 2005; Shadmehri & Khajenabi 2005, hereafter SK0; Akizuki & Fukue 2006; Shadmehri & Khajenabi 2006, hereafter SK06; Ghanbari, Salehi & Abbassi 2007). Balbus & Hawley (1998) discussed the MHD turbulence initiated by magnetorotational instability (MRI) and its effects on the angular momentum transportation.…”
Section: Introductionmentioning
confidence: 99%
“…We assume that the magnitude of is comparable to that of the turbulent viscosity (e.g., Bisnovatyi-Kogan & Ruzmaikin 1976;Shadmehri 2004). Exactly in analogy to the prescription for , we are using a similar form for the magnetic diffusivity ,…”
Section: Similarly Integration Over Z Of the Azimuthal Equation Of Mmentioning
confidence: 99%
“…However, these studies neglected the possible effects of magnetic fields. Many authors tried to construct models for a magnetized disk either in a phenomenological way based on some physical considerations (e.g., Shvartsman 1971;Lovelace et al 1994;Kaburaki 2000;Shadmehri 2004;Shadmehri & Khajenabi 2005) (2000) suggested that recent papers discussing advection-dominated accretion flow (ADAF) as a possible solution for astrophysical accretion should be treated with caution, particularly because of our ignorance surrounding the magnetic field. Models of magnetized accretion disks with externally imposed large-scale vertical magnetic field and anomalous magnetic field due to enhanced turbulent diffusion have also been studied (see, e.g., Campbell 2000;Ogilvie & Livio 2001).…”
Section: Introductionmentioning
confidence: 99%